PENGARUH RASIO PROFITABILITAS, RASIO LIKUIDITAS DAN RASIO SOLVABILITAS TERHADAP KINERJA KEUANGAN PT INDOFOOD CBP SUKSES MAKMUR Tbk - Saleh, Idris; Mainannur, Mainannur; Sari, Indah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Financial performance is the main element as a benchmark for a company, this can be seen from its financial statements. At PT Indofood CBP, Sukses Makmur Tbk (2017-2024) has experienced an increase and decrease in financial performance every year. This shows that the Company's financial performance is influenced by various factors in this study, these factors include profitability, liquidity and solvency. The formulation of the problem in this study is whether there is a simultaneous influence between the profitability ratio, liquidity ratio and solvency ratio to Financial Performance at PT. Indofood CBP Sukses Makmur Tbk in 2017-2024 and the purpose of this study is to determine the simultaneous influence between profitability ratio, liquidity ratio and solvency ratio on Financial Performance at PT. Indofood CBP Sukses Makmur Tbk in 2017-2024. The discussion in this study is related to the field of financial accounting science, in this case the approach taken is theories related to financial accounting, especially in financial performance, where later it will be discussed about the profitability ratio, liquidity ratio and solvency ratio contained in the company and its influence on financial performance. This type of research is quantitative with normality test analysis, descriptive test, classical assumption test (using multicollinearity test, heteroscedasticity test, and autocorrelation test), multiple linear regression analysis, hypothesis test (using t test and f test), R2 determination coefficient. To obtain the results of the researcher using the SPSS application version 26, the data used in this study used secondary data obtained from www.idx.co.id with the number of samples used as many as 32 samples at PT Indofood CBP sukses makmur Tbk (2017-2024). The reaseach result show that there is no effect of profitability ratios and likuidity ratios on the financial performance of PT indofood CBP sukses Makmur tbk, there is an effect of solvency ratios on the financial performance of PT indofood CBP sukses Makmur Tbk and there is a simultaneous effect of profitability ratios, likuidity ratios and solvency ratios on the financial performance of PT indofood CBP sukses Makmur Tbk.